Pain trajectories and well‐being in children and young people with cerebral palsy: A cohort study. (30th April 2022) - Shearer, Heather M.; Côté, Pierre; Hogg‐Johnson, Sheilah; Mckeever, Patricia; Fehlings, Darcy L.
Abstract: Aim: To identify 5‐week pain intensity trajectories and their association with physical and psychological well‐being in children/young people with cerebral palsy (CP). Method: A cohort study was conducted with 101 Canadian children/young people with CP, of whom 49 were female, with an overall mean age of 12 years 11 months (SD 3 years 1 month), range of 8 to 18 years, and classified in any Gross Motor Function Classification System level. Self‐reported pain intensity (Faces Pain Scale – Revised) was collected weekly for 5 weeks and physical and psychological well‐being (KIDSCREEN‐27) at baseline and 5 weeks. Statistical analyses included latent class growth and general linear models. Results: All Gross Motor Function Classification System levels were represented (I = 40.6%; II = 15.8%; III = 20.8%; IV = 13.9%; V = 8.9%). Five pain intensity trajectories were identified. Three trajectories had very low (35.4%), low (32.4%), or high (4.9%) mean stable pain. Two trajectories had moderate changing pain (16.8%) and high pain decreasing to moderate levels (10.5%) respectively. Trajectory participants with stable high pain had the lowest physical well‐being (adjusted β  = −10.01; 95% confidence interval [CI] = −19.37 to −0.66). Those in the three trajectories with the highest mean baseline pain intensity (>3 out of 10) had the lowest psychological well‐being (adjusted β  = −8.27, 95% CI = −14.84 to −1.70; β  = −6.74, 95% CI = −12.43 to −1.05; β  = −5.82, 95% CI = −15.34 to 3.71). Interpretation: Almost one‐third of participants had moderate‐to‐high pain intensity trajectories. Membership in the higher pain intensity trajectories was associated with lower physical and psychological well‐being. What this paper adds: Five distinct 5‐week pain intensity trajectories were identified in children/young people with cerebral palsy. Thirty‐two per cent of participants had moderate‐to‐high pain intensity trajectories. Participants in the trajectories with higher pain intensity reported lower physical and psychological well‐being. What this paper adds: Five distinct 5‐week pain intensity trajectories were identified in children/young people with cerebral palsy. Thirty‐two per cent of participants had moderate‐to‐high pain intensity trajectories. Participants in the trajectories with higher pain intensity reported lower physical and psychological well‐being. In this cohort study, we asked children and young people with cerebral palsy (CP) to self‐report pain intensity (Faces Pain Scale – Revised) and physical and psychological well‐being (KIDSCREEN‐27 domains) over 5 weeks. We identified five distinct short‐term pain intensity trajectories. Associations between moderate to high pain trajectory group membership and lower self‐reported physical and psychological well‐being were present after controlling for confounders. Video Podcast: https://youtu.be/monREPLNBy8 Trajetórias de dor e bem‐estar em crianças e jovens com paralisia cerebral: um estudo de coorte: Objetivo: Identificar trajetórias de intensidade de dor de 5 semanas e sua associação com o bem‐estar físico e psicológico em crianças/jovens com paralisia cerebral (PC). Método: Foi realizado um estudo de coorte com 101 crianças/jovens canadenses com PC, sendo 49 do sexo feminino, com média de idade geral de 12 anos e 11 meses (DP 3 anos 1 mês), faixa de 8 a 18 anos, e classificados em qualquer nível do Sistema de Classificação da Função Motora Grossa. A intensidade da dor autorreferida (Faces Pain Scale – Revised) foi coletada semanalmente por 5 semanas e o bem‐estar físico e psicológico (KIDSCREEN‐27) no início e 5 semanas. As análises estatísticas incluíram crescimento de classe latente e modelos lineares gerais. Resultados: Todos os níveis do Sistema de Classificação da Função Motora Grossa (GMFCS) foram representados (I = 40, 6%; II = 15, 8%; III = 20, 8%; IV = 13, 9%; V = 8, 9%). Cinco trajetórias de intensidade de dor foram identificadas. Três trajetórias tiveram muito baixa (35, 4%), baixa (32, 4%) ou alta (4, 9%) média de dor estável. Duas trajetórias apresentaram dor moderada em mudança (16, 8%) e dor alta diminuindo para níveis moderados (10, 5%), respectivamente. Os participantes com trajetória com dor alta estável tiveram o menor bem‐estar físico (β ajustado = ‐10, 01; intervalo de confiança de 95% [IC] = ‐19, 37 a ‐0, 66). Aqueles nas três trajetórias com a maior intensidade média de dor na linha de base (> 3 em 10) tiveram o menor bem‐estar psicológico (β ajustado = ‐8, 27, IC 95% = ‐14, 84 a ‐1, 70; β = ‐6, 74, 95% IC = ‐12, 43 a ‐1, 05; β = ‐5, 82, IC 95% = ‐15, 34 a 3, 71). Interpretação: Quase um terço dos participantes tiveram trajetórias de intensidade de dor moderada a alta. A participação nas trajetórias de maior intensidade de dor foi associada a menor bem‐estar físico e psicológico.